Stress and Strain on Self-Compacting Concrete using ALWA as Coarse Aggregates Substitution - Darayani, Dhiafah Hera; Aryani, Fedya Diajeng (Universitas Tribhuwana Tunggadewi Malang, 2023)
Concrete with lightweight aggregates is a type of concrete that is widely used in earthquake-prone areas. One of the building blocks for lightweight concrete utilizing waste is Styrofoam. Styrofoam in lightweight concrete began to be widely used in structural buildings. Self-compacting concrete is a type of concrete that can flow by itself without experiencing segregation. Light aggregate concrete is applied to self-compacting concrete in order to get benefits from an economic and construction time perspective, thereby saving costs and processing time. This study aimed to determine the ductility level of concrete seen from the magnitude of the stress and strain values at each ALWA content as a substitute for gravel in regular and self-compacting concrete. The loading of a concrete cylinder affects the relationship between stress and strain. Variations in the composition of ALWA substituted in concrete, from 0%, 15%, 50%, to 100%. The test was carried out as compressive strength with a cylindrical specimen with a height dimension of 200 mm and a diameter of 100 mm. The results of the test show that the strain values of 0.5f'c at SCC0, SCC15, SCC50, and SCC100 are 0.00140, 0.00140, 0.00146, 0.00151, the higher the ALWA substituted in the SCC mixture, the greater the strain value. In addition, the higher the amount of substituted ALWA in the SCC mixture, the lower the level of workability. This study shows that lightweight aggregate with Styrofoam can make concrete more ductile.ABSTRAKBeton dengan agregat ringan merupakan salah satu jenis beton yang banyak digunakan pada daerah rawan gempa. Bahan penyusun beton ringan dengan memanfaatkan limbah salah satunya berbahan Styrofoam. Penggunaan styrofoam pada beton ringan mulai banyak digunakan pada bangunan yang bersifat struktur. Beton memadat sendiri adalah jenis beton yang memiliki kemampuan untuk mengalir dengan sendirinya tanpa mengalami segregasi. Beton beragregat ringan diaplikasikan pada beton memadat sendiri agar mendapatkan manfaat dari segi ekonomi dan waktu pelaksanaan konstruksi, sehingga lebih menghemat biaya dan waktu pengerjaan. Tujuan penelitian ini untuk mengetahui tingkat daktilitas beton dilihat dari besarnya nilai tegangan dan regangan pada setiap kadar ALWA sebagai pengganti kerikil pada beton normal dan beton memadat sendiri. Pembebanan suatu silinder beton mempengaruhi hubungan antara tegangan dan regangan. Variasi komposisi ALWA yang disubstitusi pada beton yaitu dari 0%, 15%, 50% sampai 100%. Pengujian yang dilakukan berupa kuat tekan dengan benda uji berbentuk silinder dimensi tinggi 200 mm dan diameter 100 mm. Hasil dari pengujian menunjukkan nilai regangan 0.5f’c pada SCC0, SCC15, SCC50, SCC100 nilainya yaitu 0.00140, 0.00140, 0.00146, 0.00151, semakin tinggi ALWA yang disubstitusi dalam campuran SCC maka semakin besar nilai regangannya. Selain itu, semakin tinggi jumlah ALWA yang disubstitusi dalam campuran SCC maka semakin rendah tingkat workability. Penelitian ini menunjukkan penggunaan agregat ringan dengan styrofoam dapat menjadikan beton lebih daktail daripada sebelumnya.